Secondary metabolite biosynthetic diversity in Arctic Ocean metagenomes. Issue 12 (14th December 2021) - Rego, Adriana; Fernandez-Guerra, Antonio; Duarte, Pedro; Assmy, Philipp; Leão, Pedro N.; Magalhães, Catarina
Abstract : Polyketide synthases (PKSs) and non-ribosomal peptide synthetases (NRPSs) are mega enzymes responsible for the biosynthesis of a large fraction of natural products (NPs). Molecular markers for biosynthetic genes, such as the ketosynthase (KS) domain of PKSs, have been used to assess the diversity and distribution of biosynthetic genes in complex microbial communities. More recently, metagenomic studies have complemented and enhanced this approach by allowing the recovery of complete biosynthetic gene clusters (BGCs) from environmental DNA. In this study, the distribution and diversity of biosynthetic genes and clusters from Arctic Ocean samples (NICE-2015 expedition), was assessed using PCR-based strategies coupled with high-throughput sequencing and metagenomic analysis. In total, 149 KS domain OTU sequences were recovered, 36 % of which could not be assigned to any known BGC. In addition, 74 bacterial metagenome-assembled genomes were recovered, from which 179 BGCs were extracted. A network analysis identified potential new NP families, including non-ribosomal peptides and polyketides. Complete or near-complete BGCs were recovered, which will enable future heterologous expression efforts to uncover the respective NPs. Our study represents the first report of biosynthetic diversity assessed for Arctic Ocean metagenomes and highlights the potential of Arctic Ocean planktonic microbiomes for the discovery of novel secondary metabolites. The strategy employed in this study will enable future bioprospection, by identifying promising samples for bacterial isolation efforts, while providing also full-length BGCs for heterologous expression.